Body Mass Index and Anemia as Determinants of Dysmenorrhea Severity in Adolescent Girls - Lia Lajuna; Cut Sriyanti; Aniita Anita (Journal of Health Science and Medical Therapy, 2026)
Dysmenorrhea is one of the most common reproductive health problems experienced by adolescent girls and may have a negative impact on quality of life, daily activities, and academic performance. Menstrual pain that is not properly managed can lead to physical and psychological disturbances, including fatigue, decreased concentration, and school absenteeism. Several factors are known to contribute to the occurrence and severity of dysmenorrhea, particularly Body Mass Index (BMI) and anemia status, both of which are closely related to nutritional status and physiological balance during adolescence. This study aimed to examine the relationship between Body Mass Index (BMI) and anemia status with the level of dysmenorrhea pain among adolescent girls. A cross-sectional study design was employed and conducted at a public senior high school in West Aceh Regency in May 2025. A total of 138 female students from grades X and XI were selected using purposive sampling. The independent variables were BMI and anemia status, while the dependent variable was the level of dysmenorrhea pain measured using the Numeric Rating Scale (NRS). Data were analyzed using univariate and bivariate analyses, with the Chi-square test applied to assess the associations between variables. The results showed that the majority of respondents had a normal BMI (57.2%), although a considerable proportion had abnormal BMI, including underweight and overweight categories. In addition, more than half of the respondents experienced moderate anemia (51.4%). Bivariate analysis revealed a statistically significant association between BMI and the level of dysmenorrhea pain (p-value = 0.002). Furthermore, a significant relationship was also found between anemia status and dysmenorrhea pain severity (p-value = 0.001). These findings indicate that adolescent girls with abnormal BMI and anemia tend to experience more severe dysmenorrhea pain. In conclusion, Body Mass Index and anemia status play an important role in influencing the severity of dysmenorrhea among adolescent girls in West Aceh Regency.